Model Pengukuran Kinerja Entitas Syariah - - Istutik (Conference In Business, Accounting, And Management (CBAM), 2012)
Along with many kinds of Islamic Business has triggered the more Islamic entities born in Indonesia.Dewan Standar Akuntansi Syariah (DSAS) has been working hard to provide accounting standards for Islamic entities and conventional entities that implement Islamic transactions. Availability of Dewan Pengawas Syariah (DPS) in organizational structure of Islamic entitiy. Model of Organizational performance that is used for conventional entity can not simply be implemented for Islamic entity. Comitment to implement the concepts and principles of accounting and managerial should be measured and assessed in conjunction with other performance measures. Balanced scorecard has been introduced by Kaplan since 1991 for the measurement of organizational performance can be adopted for performance measurement of Islamic entities. By entering sharia perspective in four perspective of balanced scorecard, it can explained in a comprehensive of performance of Sharia entity in four perspectives, which include: financial, costumer, internal business processes, learning & growth, and in the sharia perspective. Evaluation of the performance of the Islamic entity through four perspective had have been entered with the shariaperspective in it could explain a causal relationship to encourage improvements Islamic entity, and in the long run be able to realize the vision and mission of the organization to lead realize rahmatan lil alamin.Keywords: Performance of Sharia Entity, Balanced Scorecard